ショウワ キチ シュウヘン ノ コショウ ニ オケル エイヨウ エン オヨビ DOC ノ エンチョク ブンプ - 福井, 深; フクイ, フカシ; 鳥居, 鉄也; トリイ, テツヤ; 岡部, 史郎; オカベ, シロウ; Fukui, Fukashi; Torii, Tetsuya; Okabe, Shiro (1985)
P(論文) 1977年1月から2月にかけて昭和基地周辺の淡水湖および塩湖における栄養塩と溶存有機炭素(DOC)を測定した。淡水湖の大池とスカーレン大池における栄養塩濃度は低く, 表層から底層までほぼ一定であった。塩湖のぬるめ池とすりばち池は共に不完全循環湖であり, 10m以深の無酸素層ではリン酸塩とアンモニア態窒素が著しく濃縮していた。これらの栄養塩はおそらく湖底堆積物から有機物の分解により供給されたものと推察される。淡水および塩湖におけるDOC濃度は, それぞれ0.84-2.84mg/l, および1.63-1.86mg/lの範囲を示し, 最も高い値は舟底層に見いだされた。塩湖において塩化物イオンとDOC濃度に相関性が見られたことは起源水とされる海水が低温下において濃縮する過程で溶存有機炭素も蓄積することが示唆された。 The vertical distribution of inorganic nutrients and DOC (dissolved organic carbon) was determined for two freshwater and three saline lakes near Syowa Station in January to February, 1977. In the freshwater lakes of O-like and Skallen Oike, the concentrations of nutrients were very low and their distributions were vertically homogeneous. Saline lakes of Nurume and Suribati, were typically meromictic and anoxic below 10m depth. In the anoxic layers of these lakes, PO_4-P and NH_4-N were highly concentrated. These nutrients were probably originated from the decomposition of organic materials in the bottom sediments. The concentrations of nutrients in Lake Hunazoko, which is the most saline lake around Syowa Station, were considerably lower than those of Lakes Nurume and Suribati except for SiO_2-Si. The concentration of DOC in the water of the freshwater and saline lakes ranged from 0.84 to 2.84mg/l and from 1.63 to 186mg/l, respectively. The highest value of DOC was found in the bottom of Lake Hunazoko. In the saline lakes studied, a significant correlation was found between chlorinity and DOC. This result may suggest that the high concentration of DOC in these lakes is attributable to concentration of sea water under freezing conditions. departmental bulletin paper